The hospital library as a profitable element for the organization: the investment returns - Medino Muñoz, Juan; Sebastián Viana, Tomás; Domínguez Peromingo, Montserrat; Pueyo, Ángel; Máñez Ortiz, Miguel Ángel (Revista General de Información y Documentación, 2018)
The hospital library plays a unifying role of the necessary information for its activity, not only retrospectively but also prospectively. The traditional image of the service can make difficult that assessment. The aim of this study is to expose the virtual tools developed in the Library of Hospital Universitario de Fuenlabrada in order to offer updated and relevant information as enhancement of this Department in the Organization (ROI = 276%). The conclusions reached are: the library can (must) assume a proactive role in the hospital organization; it is configured as an information service that participates and contributes to the management of the hospital knowledge, breaking its traditional image of “knowledge store”; the support of the Directorate is essential to develop that role; the existence of libraries and librarians in the hospitals is an opportunity of development; the use of indicators to measure the activity facilitates the intelligibility for the managers.